A Case of Severe Acute Respiratory Syndrome Coronavirus 2 Treatment With Remdesivir in a Hepatitis C-Coinfected Patient Resulting in Temporary Viral Control and Posttreatment Flare - da Cunha, Maria Ribeiro (Open Forum Infect Dis, 2021)
We report a case of a man with chronic hepatitis C infection treated with remdesivir for COVID-19, resulting in lowered HCV viral load, followed by a rebound after its discontinuation. Concomitant treatment with tocilizumab possibly caused loss of anti-HBs.